Faster recovery and reduced paracetamol use - a meta-analysis of EPs 7630 in children with acute respiratory tract infections - Georg Seifert; Juliette Brandes-Schramm; Andrea Zimmermann; Walter Lehmacher; Wolfgang Kamin (BMC, 2019)
Abstract Objective Fever is a very common adaptive immune response in acute respiratory tract disorders during infancy. Antipyretic / analgesic drugs such as paracetamol (acetaminophen) are widely used to improve the comfort of the child but may cause medically unneeded antipyresis and rare but potentially serious side effects. We assess whether treatment with Pelargonium sidoides extract EPs 7630 reduces the administration of paracetamol in children with acute tonsillopharyngitis (ATP) or acute bronchitis (AB). Design Meta-analysis of randomised, placebo-controlled clinical trials. Methods We searched clinical trial registries (ISRCTN, ClinicalTrials.gov) and medical literature (MEDLINE, EMBASE), for randomised, placebo-controlled trials investigating the administration of EPs 7630 to children with ATP or AB and reporting the co-administration of paracetamol. Based on the individual participant data of the eligible trials, study populations were characterized according to sex and age, and meta-analyses were performed for cumulative paracetamol use and ability to attend school at treatment end. Results Six trials including a total of 523 children aged 6-10 years (EPs 7630: 265; placebo: 258) and suffering from non-β-hemolytic streptococcal ATP (3 trials) or from AB (3 trials) were identified and eligible. Children received EPs 7630 or placebo for 6 (ATP) or 7 days (AB). Compared to placebo, EPs 7630 reduced the cumulative dose of paracetamol in 5 out of the 6 trials, by an average of 244 mg (Hedges' g; − 0.28; 95% confidence interval: [− 0.53; − 0.02]; p < 0.03). At treatment end, 30.2% (EPs 7630) and 74.4% (placebo) of the children were still unable to attend school (risk ratio: 0.43; 95% confidence interval: [0.29; 0.65]; p < 0.001). Conclusions In children aged 6-10 years with AB or ATP, EPs 7630 alleviated the symptom burden and accelerated recovery. Although EPs 7630 has no known antipyretic effect, concomitant use of paracetamol was reduced.